Potential Waste-to-Wealth Strategy for Combining Medical Surgical Gloves-Derived Pyrolysis Oil with Pentanol and Nanoparticles: Experimental Analysis on Engine Behaviors - Sathish, T.; Agbulut, Umit; Giri, Jayant; Al-lehaibi, Moaz; Hourani, Ahmad O.; Hoang, Anh Tuan (WILEY-V C H VERLAG GMBH, 2025)
In this work, the applicability of surgical glove waste pyrolysis oil (SGWPO) combined with pentanol and nano-additives (silicon dioxide (SiO2) and nano-graphene) as a substitute fuel for a 5.2 kW-diesel engine is experimentally conducted, aiming to analyze the test engine's performance and emission characteristics. Neat SGWPO could reach 8.6% less BTE, 32.24%, 18.27%, 36.17%, and 9.72% higher NOx, smoke, CO, and HC emissions than diesel at full load. However, blending SGWPO with 25% pentanol by volume and 100 ppm of SiO2 nanoparticles or 100 ppm of nanographene could improve the engine results. The obtained results of the nanographene-included SGWPO/pentanol blend are lower than SiO2-included SGWPO/pentanol blend compared to neat SGWPO. Indeed, the nano-SiO2-added SGWPO/pentanol blend demonstrated 9.72% higher BTE and 36.81%, 29.1%, 33.06%, and 25.67% reduced NOx, smoke, CO, and hydrocarbon emissions, respectively, compared to neat SGWPO. Therefore, nano-SiO2-included SGWPO/pentanol is recommended as an alternative fuel for diesel engine operation without any modifications. The recommended nanofuel blend usage in engines simultaneously supports much higher engine performance along with reduced emissions, showing the dual benefits of the waste-to-wealth strategy of surgical glove waste.
Keywords: alternative fuel; engine behavior; medical waste; nano-fuel; nanoparticles; waste-to-fuel strategy; EMISSION CHARACTERISTICS; DIESEL-ENGINE; PERFORMANCE; COMBUSTION; ADDITIVES; BUTANOL; BLENDS; Science & Technology - Other Topics